Design Study of Ship Based Nuclear Power Reactor (Core Geometry Optimization) - Dian Fitriyani Fitriyani; Zaki Su'ud (Institut Teknologi Bandung, 2005)
Preliminary design study of ship based nuclear power reactor has been performed. The results of thermo hydraulics analysis is presented and the core geometry optimization is reported. The reactors are basically lead-bistmuth cooled fast reactor using nitride fuels to enhance neutronics and safety performance. Some design modification are performed for feasibility of operation under ship dynamics caused by external forces from the marine environment such as wind, waves and tidal current that impressing reactor core performance. The basic reactor characteristics is that the power level is 100-200 MWth and excess reactivity is about 1. In this study, the steady state thermo hydraulic calculation was further performed to investigate the effect of core geometry on the design performance of the proposed ship based reactors under variation of ship oscillation about 0o– 40o. The calculation result show that balance (square) core is the convenient core geometry for the best thermo hydraulic performance optimization of design. The ship oscillations influence to balance core temperature distribution is small enough compared to low core, while pressure drop even also not as high as at tall core. The variations of total coolant flow-rate across the core are also estimated to investigate the natural circulation level and necessary pumping power for the proposed design.